Utilization of 15 N-labelled ammonium and nitrate-N by soybean (Glycine max) and wheat (Triticum aestivum) grown in Typic Haplustert - KUNDU, S; BARMAN, K K; SINGH, MUNESHWAR; TAKKAR, P N (The Indian Journal of Agricultural Sciences, 2013)
Pot culture experiment was conducted during 1992-93 winter season and 1993 rainy season to study the comparative use efficiency of ammonium-N and nitrate-N fractions of ammonium nitrate in wheat (Triticum aestivum L. emend. Fiori & Paol.) and soybean [Glycine max (L.) Merr.] grown on Typic Haplustert soil using alternate tagging tracer technique. In wheat the ratio of plant N derived from 15N tagged ammonium-N to 15N tagged nitrate-N varied from 0.75 to 0.86 against their ratio of 1.0 in the applied fertilizerÂ· indicating preference fornitrate-N over ammonium-N and thereby resulting in relatively higher use-efficiency of nitrate-N (32.9-48.8%) than ammonium-N (28.4-36.8%). While in soybean ratio varied from 1.65 to 1.96 indicating that soybean preferentially absorbed ammonium form over nitrate form of N, resulting in higber use-efficency of the ammonium-N (42.4-54.5%) than the nitrate-N (21.4-33.1 %) of the applied fertilizer.